Effectiveness of Light Emitting Diodes (LED) versus Conventional Phototherapy for Neonatal Jaundice (Bangladesh Journal of Child Health, 2018)
Background: Phototherapy is crucially an important aspect for the management of most neonatal jaundice. Neonates are prone to develop bilirubin encephalopathy (kernicterus). LED phototherapy is a new option of managing neonatal jaundice. The objective of this study is to compare the efficacy and safety of LEDs with fluorescent phototherapy in the treatment of indirect hyperbilirubinemia.Method: The study was Experimental research design, prospective study. The Study was conducted at Neonatal unit of Shaheed Suhrawardy Medical College Hospital, Dhaka. Total sample size of the study was one hundred neonates. Fifty for conventional phototherapy and fifty for LED phototherapy. Purposive sampling method was used for the study. The data collection tool of the study was pretested structured questionnaire. The modes of presentation, the clinical examination and investigation findings at admission and during daily follow up were recorded for individual patient.Result: The rate of fall of S. bilirubin was more in those neonates who have had LED phototherapy. As a result, duration of phototherapy as well as hospital stay was less in LED group. Furthermore, higher number of neonates developed rashes in LED group than in conventional group with statistically significant difference. Of course, variables regarding other adverse events did not show any statistically significant difference between two groups.Conclusion: Management of neonatal jaundice may be more effective in LED phototherapy than conventional phototherapy. LED device require shorter duration of phototherapy, thus, shorter hospital stay.Bangladesh J Child Health 2018; VOL 42 (2) :62-66